Practice of transfusing D‐positive platelets in D‐negative recipients – a reappraisal (POINT‐R). (23rd December 2015) - Dara, R. C.; Tiwari, A. K.; Arora, D.; Aggarwal, G.; Acharya, D.; Raina, V.
Abstract : Background: Many centres provide D‐mismatched platelet transfusions. Platelet concentrates may contain enough red cells leading to the formation of anti‐D antibody in D‐negative recipient. In resource‐poor settings, random donor platelet concentrate (RDPC) is used often and carries higher risk of alloimmunization. At our institution, platelets are transfused across the ABO and Rh blood group barrier without any RhIG immunoprophylaxis. In this study, we retrospectively appraised alloimmunization after D‐positive platelet transfusion in D‐negative patients. Materials and Methods: Single‐centre 5‐year data were collected from Hospital Information System (HIS) for D‐negative patients who received D‐positive platelet transfusions. Naive patients who had neither pre‐existing antibody nor received D‐positive platelet transfusion before admission were included. Those who had repeat antibody screening at least 28 days after D‐positive platelet transfusion were considered. Results: A total of 332 D‐negative patients who received 1996 D‐positive platelet transfusions were analysed. Median follow‐up was 7 weeks (range = 4–90). Anti‐D was detected in three (0·9%) D‐negative patients at 5, 8 and 24 weeks after receiving D‐positive platelet transfusions. Two of these patients received RDPCs and one received both RDPCs and single donor platelet concentrates. Conclusion: D‐positive platelet transfusion to D‐negative patients seems an acceptable practice as only 0·9% patients developed anti‐D antibody.